(3x+3)(x-6)=25x-118

Thank you for the opportunity to help you with your question!

step 1 is to expand equation on the right

(3x(x-6) + 3( x-6) =25x-118

3x^2 - 18x + 3x - 18 = 25x - 118

3x^2 - 15x - 18 = 25x - 118

Next step is to put like terms together

3x^2 - 15x - 25x - 18+ 118 = 0

3x^2 - 40x + 100 = 0

3x^2 - 30x-10x + 100 = 0

3x( x-10) -10( x-10) = 0

(3x-10) (x-10) = 0

3x-10 = 0 or x - 10 = 0

3x= 10 or x = 10

x= 10/ 3 or 10

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up